2013
DOI: 10.1007/s00167-013-2423-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of the ruptured Achilles tendon: the cost-effectiveness of open versus percutaneous repair

Abstract: This study suggests that percutaneous repair of the Achilles tendon resulted in reduced costs and yet had comparable outcome and complications rates to open repair in surgical management of the Achilles tendon. Percutaneous repair should be considered as the primary method of cost-effective surgical management of Achilles tendon rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 32 publications
(47 reference statements)
2
44
0
Order By: Relevance
“…In 1977, Ma and Griffith 8 described a percutaneous technique for the repair of acute AT rupture that became popular thereafter 19,30 . Previous evidence suggests that open compared to percutaneous repair has lower rate of re-rupture, higher rate of return to pre-injury activity level, higher complication rates, namely infection, and almost the double cost 25,31 . No significant differences were found between open and percutaneous repair in terms of muscle volume, tendon's length, and days off-work 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1977, Ma and Griffith 8 described a percutaneous technique for the repair of acute AT rupture that became popular thereafter 19,30 . Previous evidence suggests that open compared to percutaneous repair has lower rate of re-rupture, higher rate of return to pre-injury activity level, higher complication rates, namely infection, and almost the double cost 25,31 . No significant differences were found between open and percutaneous repair in terms of muscle volume, tendon's length, and days off-work 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Pre-injury level time of return was 20-40 weeks (30 average) in one study. 21 Professional athletes' average time of return to sports was 18 weeks in one study (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). 26 …”
Section: Return To Sports -Level and Time Of Returnmentioning
confidence: 99%
“…Although there is no consensus over the ideal surgical procedure for athletes, several studies suggest that percutaneous repair offers better cosmetic results, reduced costs and yet comparable functional outcome and complication rate when compared to open repair. [15][16][17] The purpose of this study is to present a review of the existing literature concerning the results of percutaneous repair of the AT rupture in athletic population with emphasis on the time and the level of return to sports activities.…”
Section: Introductionmentioning
confidence: 99%
“…Of [8] , CRETNIK A et al [9] , LIM J et al [4] , showed comparable outcome and less complication rate in comparison to open repair. In the present scenario most common cause of tendo achilles rupture is sports injury.…”
Section: Discussionmentioning
confidence: 99%